Beneficial effects of PCSK9 inhibition with alirocumab in familial hypercholesterolemia involve modulation of new immune players - Patrice Marques (Elsevier, 2022)
Familial hypercholesterolemia (FH) is associated with low-grade systemic inflammation, a key driver of premature atherosclerosis. We investigated the effects of inhibiting proprotein convertase subtilisin/kexin type 9 (PCSK9) function on inflammatory state, endothelial dysfunction and cardiovascular outcomes in patients with FH. Fourteen patients with FH were evaluated before and 8 weeks after administration of a PCSK9 blocking monoclonal antibody (alirocumab, 150 mg/subcutaneous/14 days). In vivo and ex vivo analysis revealed that alirocumab blunted the attachment of leukocytes to TNFα-stimulated human umbilical arterial endothelial cells (HUAEC) and suppressed the activation of platelets and most leukocyte subsets, which was accompanied by the diminished expression of CX3CR1, CXCR6 and CCR2 on several leukocyte subpopulations. By contrast, T-regulatory cell activation was enhanced by alirocumab treatment, which also elevated anti-inflammatory IL-10 plasma levels and lowered circulating pro-inflammatory cytokines. Plasma levels of IFNγ positively correlated with levels of total and LDL-cholesterol, whereas circulating IL-10 levels negatively correlated with these key lipid parameters. In vitro analysis revealed that TNFα stimulation of HUAEC increased the expression of PCSK9, whereas endothelial PCSK9 silencing reduced TNFα-induced mononuclear cell adhesion mediated by Nox5 up-regulation and p38-MAPK/NFκB activation, concomitant with reduced SREBP2 expression. PCSK9 silencing also decreased endothelial CX3CL1 and CXCL16 expression and chemokine generation. In conclusion, PCSK9 inhibition impairs systemic inflammation and endothelial dysfunction by constraining leukocyte-endothelium interactions. PCSK9 blockade may constitute a new therapeutic approach to control the inflammatory state associated with FH, preventing further cardiovascular events in this cardiometabolic disorder.